Nazi Medicine: In the Shadow of Reich - Michalczyk, John (Michalczyk, John, 1997)
Duration: 00:54:00 Marking the 50th anniversary of the Nuremberg Physicians the film studies the step-by-step process that led the German medical professiona down an unethical road to genocide. It graphically documents the racial theories and eugenics principles that set the stage for the doctors' participation in sterilization and euthanasia, the selections at the death camps, as well as gruesome medical experimentations involving camp inmates.